Analisis Budaya Organisasi, Disiplin Kerja, dan Intellectual Capital terhadap Pelayanan Publik melalui Work Engagement - Fadhel Kusuma; Umi Rusilowati; Endang Sugiarti (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the effects of organizational culture, work discipline, and intellectual capital on public service through work engagement among government employees in Pancoran Mas District, Depok City. A quantitative explanatory approach with a causal design was applied using a census of 110 employees from the district office and six subdistrict offices. Data were collected through observation and a five-point Likert questionnaire and analyzed using PLS-SEM with SmartPLS 4. Organizational culture, work discipline, and intellectual capital had positive and significant effects on work engagement (beta = 0.376, 0.365, and 0.271) and public service (beta = 0.258, 0.266, and 0.295). Work engagement positively affected public service (beta = 0.339). The respective indirect effects through work engagement were 0.127, 0.124, and 0.092, and all were significant. The model explained 47.3% of work engagement and 67.5% of public service. Thus, work engagement served as a complementary partial mediator between the three organizational resources and public service.